A Mini Review of High-Performance Supercapacitors Derived Metal-Organic Frameworks: Current Challenges and Potentials - Ab Ghani, Mohd Hafizuddin; Ismail, Ismayadi; Nawang, Rosnah; Mat Nong, Mohd Ali; Razali, Siti Zulaika; Rashid, Umer; Hazmi, Balkis; Liew, Josephine Ying Chyi; Mohamad Jaafar, Adila; Rajendran Royan, Nishata Royan; Chen, Ruey Shan (Journal of Emerging Technologies and Industrial Applications, 2024)
The persistent rise in fossil fuel consumption has heightened the greenhouse effect, posing a substantial threat to both human well-being and the environment. To counteract the global energy shortage and pollution crisis, there is an imperative to develop renewable and clean energy sources. Technological advancements in net-zero energy conversion and climate-neutral storage systems are gaining prominence. In recent decades, there has been a noteworthy surge in interest and significant efforts directed towards advancing new technologies, particularly in the realm of enhancing the efficiency of energy storage devices like batteries and capacitors. However, inherent drawbacks in batteries, such as low power density and limited charge/discharge cycles, and the low energy density of traditional capacitors, have restricted their utilization in high-technology applications. This limitation has spurred the emergence of the high-performance supercapacitor concept. Researchers in both industry and academia are keen on exploring energy conversion and storage systems characterized by exceptional stability and efficiency, presenting a substantial challenge in their construction and design. This mini review specifically delves into recent progress in supercapacitor applications derived from Metal-Organic Frameworks (MOFs), addressing both current challenges and its future potential.